Search for light Higgs bosons from supersymmetric cascade decays in pp collisions at ?s=13TeV - Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Damanakis, K.; Dragicevic, M. (Springer, 2023)
A search is reported for pairs of light Higgs bosons (H-1) produced in supersymmetric cascade decays in final states with small missing transverse momentum. A data set of LHC pp collisions collected with the CMS detector at root s = 13 TeV and corresponding to an integrated luminosity of 138 fb(-1) is used. The search targets events where both H-1 bosons decay into b (b) over bar pairs that are reconstructed as large-radius jets using substructure techniques. No evidence is found for an excess of events beyond the background expectations of the standard model (SM). Results from the search are interpreted in the next-to-minimal supersymmetric extension of the SM, where a singlino of small mass leads to squark and gluino cascade decays that can predominantly end in a highly Lorentz-boosted singlet-like H-1 and a singlino-like neutralino of small transversemomentum. Upper limits are set on the product of the squark or gluino pair production cross section and the square of the b (b) over bar branching fraction of the H1 in a benchmark model containing almost mass-degenerate gluinos and light-flavour squarks. Under the assumption of an SM-like H-1 -> b (b) over bar branching fraction, H-1 bosons with masses in the range 40-120 GeVarising from the decays of squarks or gluinos with a mass of 1200-2500 GeV are excluded at 95% confidence level.